2021
DOI: 10.1186/s12870-021-02994-8
|View full text |Cite
|
Sign up to set email alerts
|

IDA (INFLORESCENCE DEFICIENT IN ABSCISSION)-like peptides and HAE (HAESA)-like receptors regulate corolla abscission in Nicotiana benthamiana flowers

Abstract: Background Abscission is an active, organized, and highly coordinated cell separation process enabling the detachment of aerial organs through the modification of cell-to-cell adhesion and breakdown of cell walls at specific sites on the plant body known as abscission zones. In Arabidopsis thaliana, abscission of floral organs and cauline leaves is regulated by the interaction of the hormonal peptide INFLORESCENCE DEFICIENT IN ABSCISSION (IDA), a pair of redundant receptor-like protein kinases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 61 publications
0
6
0
1
Order By: Relevance
“…Further elucidation of how the activity of MSD2 or the expression of MSD2 is regulated under various environmental conditions is necessary for a comprehensive understanding of the biological significance of ROS metabolism regulated by MSD2. Reactive oxygen species and IDA-HAE are involved in cell separation and responses to stress in various cell types, the mechanisms of which are conserved in various plants (Tucker & Yang, 2012;Ventimilla et al, 2020Ventimilla et al, , 2021, suggesting that our findings should be applicable to other cell types and other plant species, including crops. Protein concentration is often controlled not only through synthesis but also through the balance of synthesis and degradation (Vierstra, 1993), which has the advantage of being able to respond quickly to needs.…”
Section: New Phytologistmentioning
confidence: 83%
See 1 more Smart Citation
“…Further elucidation of how the activity of MSD2 or the expression of MSD2 is regulated under various environmental conditions is necessary for a comprehensive understanding of the biological significance of ROS metabolism regulated by MSD2. Reactive oxygen species and IDA-HAE are involved in cell separation and responses to stress in various cell types, the mechanisms of which are conserved in various plants (Tucker & Yang, 2012;Ventimilla et al, 2020Ventimilla et al, , 2021, suggesting that our findings should be applicable to other cell types and other plant species, including crops. Protein concentration is often controlled not only through synthesis but also through the balance of synthesis and degradation (Vierstra, 1993), which has the advantage of being able to respond quickly to needs.…”
Section: New Phytologistmentioning
confidence: 83%
“…HAE/ HSL2 work with the other receptor-like proteins SOMATIC EMBRYOGENESIS RECEPTOR-LIKE KINASEs (SERKs), including SERK1-4, to form complexes upon interaction with IDA to initiate floral abscission (Meng et al, 2016). The IDA-HAE pathway is conserved in various crop species such as tomato (Solanum lycopersicum), soybean (Glycine max), and tobacco (Nicotiana tabacum) and is involved in organ abscission (Tucker & Yang, 2012;Ventimilla et al, 2020Ventimilla et al, , 2021. However, the IDA-HAE module is not limited to floral organ abscission, as it also participates in other cell separation processes such as lateral root emergence and root cap detachment (Kumpf et al, 2013; 2466 New Phytologist (2022) 235: 2466-2480 Ó 2022 The Authors New Phytologist Ó 2022 New Phytologist Foundation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that there is substantial genetic variation underlying abscission across the plant kingdom based on differences in the morphology and bulk transcriptome of AZs. Nevertheless, a recent report showed that Nicotiana lines with silenced HAE and IDA orthologs exhibited reduced perianth abscission 41 . In addition, expression of both citrus ad litchi orthologs of IDA can complement the abscission-deficient ida mutant phenotype in Arabidopsis 42,43 .…”
Section: Discussionmentioning
confidence: 98%
“…A number of transcription factors have been implicated in regulating AZ development and abscission signaling 14,[28][29][30][31] . It has been shown that Nicotiana lines with silenced HAE and IDA orthologs exhibit reduced perianth abscission 32 , and expression of both citrus ad litchi orthologs of IDA can complement the abscission-deficient ida mutant phenotype in Arabidopsis 33,34 . We have also demonstrated abscission of Arabidopsis cauline leaves upon water stress or pathogen infection is under similar genetic control as floral abscission 35,36 .…”
Section: Introductionmentioning
confidence: 99%
“…This process could be related to a decrease in the expression of the cell wall remodeling enzymes, thus suggesting it is involved in cell separation during flower dehiscence, in a regulation mechanism mediated by the IDA signaling [ 63 ]. Recent work in Nicotiana benthamiana showed that the overexpression of NbenIDA1A gene generated shorter corollas, premature senescence of this whorl, and corolla abscission was also accelerated [ 64 ]. On the other hand, the double mutant hae hsl2 generates flowers that do not open after pollination [ 65 ].…”
Section: Other Cell Wall Proteinsmentioning
confidence: 99%